Literature Study: Mountain Scrubbing as Landslide and Flash Flood Disaster Mitigation Based on Local Wisdom in Java - Khoirotul Ummah; Nur Aisyah; Vina Rachma Yunita; Wahyu Bunga Anjani; Nasywa Nabilah Azzahra (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Indonesia is one of the countries with the highest disaster vulnerability in the world, particularly to flash floods and landslides due to its geographical conditions dominated by hilly areas, high rainfall, and land use changes. In this context, local wisdom plays a crucial role as an adaptive and sustainable community-based mitigation strategy. One form of local wisdom that is often used is Nyabuk Gunung, a technique for managing sloping land by following contour lines to resemble a